Optimized Inhibitors of MDM2 via an Attempted Protein‐Templated Reductive Amination. (12th December 2019) - van der Vlag, Ramon; Yagiz Unver, M.; Felicetti, Tommaso; Twarda‐Clapa, Aleksandra; Kassim, Fatima; Ermis, Cagdas; Neochoritis, Constantinos G.; Musielak, Bogdan; Labuzek, Beata; Dömling, Alexander; Holak, Tad A.; Hirsch, Anna K. H.
Abstract: Innovative and efficient hit‐identification techniques are required to accelerate drug discovery. Protein‐templated fragment ligations represent a promising strategy in early drug discovery, enabling the target to assemble and select its binders from a pool of building blocks. Development of new protein‐templated reactions to access a larger structural diversity and expansion of the variety of targets to demonstrate the scope of the technique are of prime interest for medicinal chemists. Herein, we present our attempts to use a protein‐templated reductive amination to target protein‐protein interactions (PPIs), a challenging class of drug targets. We address a flexible pocket, which is difficult to achieve by structure‐based drug design. After careful analysis we did not find one of the possible products in the kinetic target‐guided synthesis (KTGS) approach, however subsequent synthesis and biochemical evaluation of each library member demonstrated that all the obtained molecules inhibit MDM2. The most potent library member ( K i =0.095 μm ) identified is almost as active as Nutlin‐3, a potent inhibitor of the p53‐MDM2 PPI. Abstract : Templated potential : Herein, we present our attempts to use a protein‐templated reductive amination to target protein–protein interactions (PPIs). After careful analysis, we did not find one of the possible products in the kinetic target‐guided synthesis (KTGS) approach. Subsequent synthesis and biochemical evaluation of each library member demonstrated that all the obtained molecules inhibit MDM2. The most potent library member ( K i =0.095 μm ) identified is almost as active as Nutlin‐3, a potent inhibitor of the p53‐MDM2 PPI.